2022
DOI: 10.1016/j.jhepr.2021.100389
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-targeted genome editing of human induced pluripotent stem cell-derived hepatocytes for the treatment of Wilson’s disease

Abstract: Background & Aims Wilson’s disease (WD) is an autosomal recessive disorder of copper metabolism caused by loss-of-function mutations in ATP7B , which encodes a copper-transporting protein. It is characterized by excessive copper deposition in tissues, predominantly in the liver and brain. We sought to investigate whether gene-corrected patient-specific induced pluripotent stem cell (iPSC)-derived hepatocytes (iHeps) could serve as an autologous cell source for cellular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Therefore, novel therapeutic approaches were warranted to improve the management of neuropsychiatric symptoms. In this context, several animal studies have generated promising results ( 6 , 11 , 12 ). However, there are no ongoing reported clinical studies in neurological-type WD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, novel therapeutic approaches were warranted to improve the management of neuropsychiatric symptoms. In this context, several animal studies have generated promising results ( 6 , 11 , 12 ). However, there are no ongoing reported clinical studies in neurological-type WD patients.…”
Section: Discussionmentioning
confidence: 99%
“…This unsatisfying result was also supported by previous studies. [ 19 , 20 , 21 , 22 , 23 ] The low repopulation efficiency for HLCs transplantation was possibly due to the immature state of hepatic differentiation. Other candidates of cell sources like hepatic transdifferentiation from somatic cells and immortalization of hepatocytes show safety issues like oncogenic transformation or other unpredictable risks.…”
Section: Discussionmentioning
confidence: 99%
“… 93 Another group showed that gene-corrected HLCs from patients with Wilson disease could slow the manifestation of Wilson disease in a mouse model following implantation. 94 …”
Section: Applications Of Hlcs In Disease Modelingmentioning
confidence: 99%